IMPACT OF OREGANO AND HIBISCUS SABDARIFFA ESSENTIAL OILS ON THE SPOILAGE INDEX AND SENSORY CHARACTERISTICS OF KAURMA - N. A. Mirzan (مجلة الأنبار للعلوم الزراعية)
Kaurma, a traditional Kurdish meat product, contains a high percentage of fats (30–40%) and is highly susceptible to lipid oxidation and microbial spoilage during storage, which drastically reduces its shelf life and commercial potential. Due to the increasing demand for natural food preservatives, this study investigates the effectiveness of oregano and Hibiscus sabdariffa essential oils as natural additives in improving the oxidative, microbial, and sensory stability of kaurma stored under refrigeration. The kaurma samples were divided into four groups: control (no essential oils), oregano oil (1%), Hibiscus sabdariffa oil (1%), and a combination of both oils (0.5% each). Lipid oxidation, as measured by chemical analyses (peroxide value and thiobarbituric acid-reactive substances (TBARS), was lower in the groups treated with essential oils than in the control (p < 0.05). Microbial analysis revealed their antimicrobial properties as evidenced by reduced total viable counts and inhibition of mold and yeast growth in the treated samples. Sensory analysis showed improvements in flavor, texture, and general acceptability among the groups, with the highest scores for those treated with oregano oil. These results show that oregano and Hibiscus sabdariffa essential oils are effective natural preservatives for extending the shelf life of high-fat meat products as well as can be viable substitutes for synthetic additives.